If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying y + 2x + 1 = -6x + 4 Reorder the terms: 1 + 2x + y = -6x + 4 Reorder the terms: 1 + 2x + y = 4 + -6x Solving 1 + 2x + y = 4 + -6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6x' to each side of the equation. 1 + 2x + 6x + y = 4 + -6x + 6x Combine like terms: 2x + 6x = 8x 1 + 8x + y = 4 + -6x + 6x Combine like terms: -6x + 6x = 0 1 + 8x + y = 4 + 0 1 + 8x + y = 4 Add '-1' to each side of the equation. 1 + 8x + -1 + y = 4 + -1 Reorder the terms: 1 + -1 + 8x + y = 4 + -1 Combine like terms: 1 + -1 = 0 0 + 8x + y = 4 + -1 8x + y = 4 + -1 Combine like terms: 4 + -1 = 3 8x + y = 3 Add '-1y' to each side of the equation. 8x + y + -1y = 3 + -1y Combine like terms: y + -1y = 0 8x + 0 = 3 + -1y 8x = 3 + -1y Divide each side by '8'. x = 0.375 + -0.125y Simplifying x = 0.375 + -0.125y
| 258-4x=41x+23 | | 3(2x+3)=33 | | 5m-1=49 | | 5x+1-x=-27 | | 7(x+4)=7(x+6) | | 10x-1=7x+5 | | 4(x-2)-3=10 | | 4n+24=8n | | 100=7x+6x-4 | | 10p-11=-4p+5 | | 9x-142=3x-10 | | 0.4(x+10)+0.2x=13 | | 3-2x+5=2(2x-3) | | 10p-11=4p | | -6x+2=-70 | | 4n+21=n | | 9x-17=3x-1 | | 2x-17y=13 | | 80=8(s+7) | | 5n+2n=6 | | -8-3-x=10-9x | | 7+2p-6=8p+10-5p | | 24=33(2-2x) | | x^3-10x-8=0 | | 8(3w-8)=4(6w+4) | | 17a+48=20a+30 | | x-17=142 | | 14c+5d-7c= | | 2x-4=-36 | | 5x+34=7x+10whatisx | | 0.15x=7.20 | | 3x-15=66 |